Credibility effect in online news: media-rhetoric perspective (based on color terms use) - Lukianets, Halyna (My University, 2022)
Стаття присвячена створенню ефекту довіри до онлайн-новин за допомогою використання базових колірних термінів при зверненні до правдоподібності, експертності та репутації. По-перше, ідентифіковано історичні зміни мети риторики та встановлено співвідношення між переконливістю та достовірністю. По-друге, теми винаходу, а саме визначення, поділ, взаємозв’язок, обставини та свідчення, вивчаються з точки зору створення ефекту достовірності. The article deals with creating credibility effect in online news by means of using basic color terms when appealing to believability, expertise and reputation. First, historical changes of rhetoric aim are identified and the correlation between persuasiveness and credibility is established. Second, the topics of invention, namely definition, division, relationship, circumstance and testimony, are studied from the perspective of creating effect of credibility.
Keywords: категоризація кольорів; ефект достовірності; теми винаходу; переконливість; звернення до правдоподібності; color categorization; credibility effect; topics of invention; persuasiveness; appeal to believability; кафедра іноземних мов професійного спрямування